Analisis Faktor Risiko Kejadian ISPA pada Balita di Wilayah Kerja Puskesmas Kapan - Margareta Abainpah; Sir, Amelya B.; Riwu, Yuliana Radja (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Acute Respiratory Infection (ARI) is a health issue that needs attention as it is a leading cause of death among toddlers in several developing countries, including Indonesia.are more vulnerable to diseases than adults because their immune systems are still developing. One of the infectious diseases frequently experienced by toddlers is ARI (WHO, 2022). The purpose of this research is to analyze the factors related to the incidence of ARI in toddlers in the Kapan Health Center working area. This is an analytical observational study with a cross-sectional design, involving all children aged 1-4 years from January to June. The sampling technique used is simple random sampling. The research results show a relationship between nutritional status and the incidence of ARI in toddlers (p-value = 0.000), a relationship between low birth weight (LBW) and the incidence of ARI in toddlers (p-value = 0.000), a relationship between immunization status and the incidence of ARI in toddlers (p-value = 0.000), no relationship between exclusive breastfeeding and the incidence of ARI in toddlers (p-value = 0.340), and a relationship between the use of cooking fuel and the incidence of ARI in toddlers (p-value = 0.003). The community is expected to improve children's nutritional status, actively engage in health services such as posyandu and socialization, and implement healthy living behaviors, such as not bringing children into the kitchen while cooking, ensuring proper kitchen ventilation, and maintaining environmental cleanliness to reduce the risk of ARI in toddlers.